2021
DOI: 10.5194/hess-25-551-2021
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impacts of compound extremes on agriculture

Abstract: Abstract. Agricultural production and food prices are affected by hydroclimatic extremes. There has been a growing amount of literature measuring the impacts of individual extreme events (heat stress or water stress) on agricultural and human systems. Yet, we lack a comprehensive understanding of the significance and the magnitude of the impacts of compound extremes. This study combines a fine-scale weather product with outputs of a hydrological model to construct functional metrics of individual and compound … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…This translates to a growing risk of extreme heat stress (Coffel et al 2018, Li et al 2020)-the combination of temperature and other climate variables, like humidity, known to negatively affect the human body's functioning in hot weather-with major implications for human health (Hanna and Tait 2015, Kjellstrom et al 2016, Mora et al 2017. The effect of high temperatures on water and energy supply and demand, ecosystems, and economic and agricultural output can also be relatively larger or smaller according to the co-occurring humidity (Dunne et al 2013, Harpold and Brooks 2018, Haqiqi et al 2021. Even regions with comparatively mild climates can be strongly affected by heat stress due to a lack of physiological, behavioral, or infrastructural preparedness, stemming from resource limitations or perceived lack of need for investments such as air conditioning or heatresistant materials (Ferranti et al 2016, Guirguis et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…This translates to a growing risk of extreme heat stress (Coffel et al 2018, Li et al 2020)-the combination of temperature and other climate variables, like humidity, known to negatively affect the human body's functioning in hot weather-with major implications for human health (Hanna and Tait 2015, Kjellstrom et al 2016, Mora et al 2017. The effect of high temperatures on water and energy supply and demand, ecosystems, and economic and agricultural output can also be relatively larger or smaller according to the co-occurring humidity (Dunne et al 2013, Harpold and Brooks 2018, Haqiqi et al 2021. Even regions with comparatively mild climates can be strongly affected by heat stress due to a lack of physiological, behavioral, or infrastructural preparedness, stemming from resource limitations or perceived lack of need for investments such as air conditioning or heatresistant materials (Ferranti et al 2016, Guirguis et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been reported that US economic agricultural losses between 1980 and 2012 were 4 times larger during hot and dry (hot-dry) conditions compared with during drought events alone (Suzuki et al, 2014). Moreover, the response to multiple climatic stressors is complex and can be subject to interaction effects where climatic drivers create more damage in combination than the sum of each in isolation (Ben-Ari et al, 2018;Haqiqi et al, 2021;Matiu et al, 2017;Rigden et al, 2020). Interestingly, multiple climatic stressors can also result in positive interactions with beneficial effects on crop yields (Carter et al, 2016;Suzuki et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Compound hydrometeorological extremes (e.g., hot and drought compound) exert profound impacts on agriculture and water irrigation demand (Zampieri et al, 2017;Lu et al, 2018;Ribeiro et al, 2020b;Haqiqi et al, 2021;Vogel et al, 2021). For example, the compound drought and heatwave events may affect socioecological systems (Mukherjee et al, 2020), wildfires (Abatzoglou and Williams, 2016;AghaKouchak et al, 2020;Sutanto et al, 2020), air pollution (Tressol et al, 2008;Zhang H. et al, 2017;Wang et al, 2017;Lin et al, 2020), heat-related deaths (D'Ippoliti et al, 2010;Mitchell et al, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 99%